HUBUNGAN KESIAPAN BELAJAR DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR BAHASA INDONESIA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI 7 MANDAU - Hamidah Tusya’ Diah; Hasnah Faizah; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations and preliminary interviews with Indonesian language subject teachers and seventh grade students at 7 Mandau State Middle School, it was known that the class had not yet succeeded in achieving the minimum completeness criteria (KKM) on school-determined daily tests of 75. Students who achieved the minimum completeness criteria (KKM) only amounted to 120 students from 209 students or only 57.4%. Whereas, learning outcomes are said to be good if students have reached KKM as much as 60% -75%. Referring to the national KKM standard set by the Ministry of Education and Culture. This study aims to describe the relationship of learning readiness to student learning outcomes at Mandau 7 Public Middle School and describe the relationship of achievement motivation to student learning outcomes at Mandau 7 Public Middle School. The instrument was made according to the variable measurement standards, while the theory adopted by the researcher for the learning readiness variable was from Soemanto, and the achievement motivation variables were taken from McClelland's theory. The principle of measurement and scale used in this study is the Likert Scale. Observations were made to obtain Indonesian learning outcomes obtained in a study sample. Data analysis is intended to test the truth of the hypothesis. The data analysis technique used in this study is correlational analysis. Before hypothesis testing is carried out, validity and reliability tests are carried out. Based on the results of the research and the objectives to be achieved, it can be concluded that there is a relationship between learning readiness and the learning outcomes of Indonesian students at Mandau 7th Middle School with the strength of the relationship in the strong category and there is a correlation between achievement motivation and Indonesian language learning outcomes at Mandau 7th Public Relations in the medium category.Key Words: Learning Readiness, Achievement Motivation, and Indonesian Language Learning Outcomes